Land tenure in Ethiopia: Continuity and change, shifting rulers, and the quest for state control - Crewett, Wibke; Bogale, Ayalneh; Korf, Benedikt (International Food Policy Research Institute, 2008)
Ethiopia experiences a fierce political debate about the appropriate land tenure policy. After the fall of the socialist derg regime in 1991, land property rights have remained vested in the state and only usufruct rights have been alienated to farmers – to the disappointment of international donor agencies. This has nurtured an antagonistic debate between advocates of the privatization of land property rights to individual plot holders and those supporting the government’s position. This debate, however, fails to account for the diversity and continuities in Ethiopian land tenure systems. This paper reviews the changing bundles of rights farmers have held during various political regimes in Ethiopia, the imperial, the derg and the current one, at different times and places. Our analysis indicates the marked differences in tenure arrangements after the fall of the empire, but identifies some commonalities in land tenure regimes as well, in particular between the traditional rist system and the current tenure system.